(untitled) (Research, Society and Development, 2020)
With technological advances, the world is increasingly connected and information is able to reach a very large number of people, enabling the expansion of knowledge, raising questions about the influence of the media on violent attitudes and changes in people’s behavior. This integrative review of the literary writer aimed to characterize the responsibility of media outlets as collaborators for the dissemination of violent social acts against themselves and others. The present study is a bibliographic search of the type integrative literature review. For the location of relevant studies that answered the research question, descriptors indexed in Portuguese, English and Spanish were used. The descriptors were obtained from the Medical Subject Headings (MESH), from the Health Sciences Descriptors (DeCS). It can be observed that as members have a high influence, not behavior of risk of their users, due to the ease of access to publications of risk such as self-flagellation, use of alcohol and drugs, and mainly on the most vulnerable, such as young people and people com psychological problems. Faz-it is necessary to potentiate the exhibition of reflective atos and positive content to serve as a reference to society and promote the prevention of atitutes hostis. At the same time it must provide social transformation and harmony between the members of the society, fighting violence by means of preventive and / or interventional proposals through contributions of Psychology and of their professionalism.